Left-sided gallbladder in a 17-year-old male: A case report - William G. Lee; Shannon T. Wong-Michalak; Eveline H. Shue; Eugene S. Kim; Christopher T. Watterson; Juan Carlos Pelayo (Elsevier, 2024)
Introduction: Left-sided gallbladder (LSG) is a rare anatomic variant in the pediatric population where the gallbladder lies to the left of the round ligament. The diagnosis of LSG is often made intraoperatively as preoperative imaging has poor sensitivity for detection. As LSG is also associated with biliary and vascular anatomic variation, lack of familiarity with these anatomic variants can lead to higher rates of bleeding and bile duct injury. Case presentation: A 17-year-old previously healthy male with history of scoliosis and sickle cell trait was referred for surgical management of symptomatic cholelithiasis. The patient had presented with multiple transient episodes of severe epigastric pain and nausea with ultrasound findings of cholelithiasis. There was no comment on the ultrasound report of any anatomic variation or abnormal location of the gallbladder. However, review of the imaging demonstrated a gallbladder that was situated on the left side of the liver and medial to ligamentum teres hepatis (round ligament). During the laparoscopic cholecystectomy, we confirmed that the gallbladder was located to the left of the round ligament and inferior to segment III of the liver. A retrograde top-down approach was utilized to clearly delineate the cystic artery and duct. The cystic artery was identified by its entry point into the gallbladder crossing anterior to the common bile duct in a right-to-left fashion. The cystic duct was identified and noted to drain into the right-side of the common hepatic duct. Due to clear delineation of the gallbladder anatomy with this approach, intraoperative cholangiography or fluorescence cholangiography were not utilized. He was discharged on postoperative day one without any complications. Conclusion: LSG is associated with biliary and vascular anomalies, which may lead to intraoperative complications. Therefore, the biliary anatomy should be clearly elucidated prior to proceeding with cholecystectomy in cases of LSG.